Challenges in diagnosing the Human T-Cell Lymphotropic Virus type 1 and type 2 (HTLV-1 and HTLV-2) in patients infected with HIV-1 - Rodrigues Campos, Karoline (2022)
Since the 90 decade, the Instituto Adolfo Lutz (IAL) has performed the diagnosis of Human T-cellLymphotropic Virus type 1 and type 2 (HTLV-1and HTLV-2), and thenceforth the difficulties indiagnosing HTLV-2 have been reported, mostly in HIV-infected patients. The present study aimedat evaluating the several diagnostic techniques currently available (commercial kits and in-houseassays), and to establish the best algorithm to be employed for diagnosing HTLV-1/-2 in patientsinfected with HIV-1. The study population was composed by two patient groups attended at HIV/AIDS specialized services care in São Paulo: the pioneer one [Group 1 (G1), n=1,608], and theother with the most recent historical health setting [Group 2 (G2), n=1,383. The majority of theboth groups were composed by male patients [G1 (76.9%) and G2 (67.2%)], with average agesof 44.3 (G1) and 35.6 (G2) years old. The assays employed for HTLV-1/-2 screening in 2,991blood samples were the 3rd generation enzyme immunoassays (Murex and Gold ELISA); and thosereagent samples were subsequently confirmed by Western Blot (WB) and INNO-Lia (LIA), andby means of two molecular methodologies, real-time PCR (qPCR – pol) and nested-PCR-RFLP(tax). Samples were considered HTLV-1/-2 positive when they showed specific reactivity, at leastin one of the four confirmatory assays used in this study. HTLV-1/-2 prevalence of 3.1% (G1) and4.2% (G2) were detected. Differences in sex (G2) and average age among the HIV-mono-infectedindividuals and the HIV/HTLV-co-infected patients were found. Among the co-infected patients,47.0% (G1) and 51.7% (G2) were female, and the average age was higher in G1 (49.5 vs. 43.5 yearsold). By serological screening, 127 sera samples were reagent, and the truly HTLV infection wasconfirmed in 108 samples, being 56 HTLV-1 [G1 (27) + G2 (29)], 45 HTLV-2 [G1 (21) + G2 (24)],one HTLV-1 + HTLV-2 double infection (G2) and six HTLV [G1 (2) + G2 (4)]. Of 19 reactive bloodsamples at screening assay, nine remained indeterminate (G2), and ten were considered negative[G1 (1) + G2 (9)]. The confirmatory assays employed for analyzing the blood samples from thepatients included in the present study with better sensitivity values was LIA (97.2%). The obtainedresults confirmed that none of the confirmatory tests showed 100% sensitivity in detecting HTLV1/-2 in samples from HIV-infected patients; thus, the use of combined tests should be crucial.Accordingly, the best cost-effective algorithm to be applied for testing these patients should be byemploying qPCR as the first choice, and followed by LIA to analyze the negative samples.